Spatial and temporal variability of oxidative stress indicators in the red crab (Pleuroncodes planipes) from the west coast of the Baja California Peninsula, Mexico - Orlando Martínez-Canto; Norma Olimpia Olguín-Monroy; Juan Antonio de Anda-Montañez; Tania Zenteno-Savín (Ciencias Marinas, 2012)
The red crab Pleuroncodes planipes is a resource with the potential for commercial exploitation. Red crabs have an elevated antioxidant capacity, which is subject to spatial and temporal variability. The objective of this study was to evaluate the variability of the oxidative stress indicators in P. planipes collected on four research cruises off the western coast of the Baja California Peninsula (Mexico). Superoxide radical (O2•–) production, lipid peroxidation, and antioxidant enzyme activities were quantified in muscle and hepatopancreas of the collected specimens. Significantly higher O2•– production and antioxidant enzyme activities were found in hepatopancreas than in muscle (P < 0.05), which reflects the specific function of each tissue. Statistically significant differences (P < 0.05) in oxidative stress indicators were found among sampling stations. The results suggest that P. planipes is more susceptible to oxidative damage when sea temperature is warmer, particularly during El Niño conditions.